Analysis of student engagement in online learning in Indonesia using a self determination theory approach - Laksana, Muhammad Adam; Pranitasari, Diah; Sampurna, Dian Surya (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
The aims to analyze student engagement in online learning in Indonesia using a self-determination theory approach. This research uses a quantitative type of research. The population in this study were undergraduate management students who were or had previously conducted online learning. The sampling technique used random sampling where the total sample was 130 respondents. Data collection was obtained by distributing questionnaires distributed via Google Form. The data analysis method uses SmartPLS 4.0 software to carry out outer model tests (convergent validity, discriminant validity, AVE, composite reliability, and Crobach's alpha), inner model tests (model fit), and hypothesis tests. The results of this research show that social relationships have no effect on cognitive engagement, while other indicators influence each other. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.